2015
DOI: 10.1159/000373994
|View full text |Cite
|
Sign up to set email alerts
|

CTGF Positively Regulates BMP12 Induced Tenogenic Differentiation of Tendon Stem Cells and Signaling

Abstract: Background/Aims: Disordered differentiation of tendon stem cells (TSCs) during repair of injured tendon can result in the pathogenesis of chronic tendinopathy. Understanding tenocyte differentiation may provide new therapeutic insights for the prevention and treatment of chronic tendinopathy. The aim of our study was to determine if CTGF exerts a similar effect on BMP12-driven differentiation of rat TSCs. Methods: In overexpressing and RNA interference CTGF TSCs, tenogenic differentitation and the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…In addition, transplantation of CD146 + TSCs treated by CTGF short-term was able to induce tendon regeneration (Supplemental Figure 11, C and F), whereas scar-like tissue with disrupted collagens formed when CD146 -or untreated CD146 + tendon cells were delivered (Supplemental Figure 11, A The TGF-β pathway has been reported to play critical roles in tendon development (50). A recent in vitro study suggested a potential link between CTGF and BMP12 in tenogenic differentiation of rat flexor TSCs (51). Although we have demonstrated that the FAK/ERK1/2 pathway regulates CTGF's function in CD146 + TSCs using siRNA KD, it is unclear how CTGF-regulated tenogenic differentiation is linked with signaling mediated by TGF-β and/or BMPs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, transplantation of CD146 + TSCs treated by CTGF short-term was able to induce tendon regeneration (Supplemental Figure 11, C and F), whereas scar-like tissue with disrupted collagens formed when CD146 -or untreated CD146 + tendon cells were delivered (Supplemental Figure 11, A The TGF-β pathway has been reported to play critical roles in tendon development (50). A recent in vitro study suggested a potential link between CTGF and BMP12 in tenogenic differentiation of rat flexor TSCs (51). Although we have demonstrated that the FAK/ERK1/2 pathway regulates CTGF's function in CD146 + TSCs using siRNA KD, it is unclear how CTGF-regulated tenogenic differentiation is linked with signaling mediated by TGF-β and/or BMPs.…”
Section: Discussionmentioning
confidence: 96%
“…Osteogenic, chondrogenic, and adipogenic differentiation were induced by applying differentiation media, as per our prior methods (6,37,38). Osteogenic differentiation medium contained 100 nM dexamethasone, 10 mM β-glycerophosphate, and 0.05 mM l-ascorbic acid 2-phosphate (SigmaAldrich) per our prior methods (12,51). Chondrogenic medium was supplemented with 10 ng/ml transforming growth factor-β3 (TGF-β3) (R&D Systems).…”
Section: Discussionmentioning
confidence: 99%
“…Tendon stem cells (TSCs), prone to osteogenic differentiation under excessive tension, present a high multi-differentiation potential, self-renewal capacity, and low immunogenicity [18, 19], and disordered differentiation of TSCs in the repair of injured tendon might lead to the pathogenesis of chronic tendinopathy [20]. The metaplasia of adipose tissue appeared in the ruptured tendon demonstrates that Dex could induce TSCs to differentiate into adipocytes, while the mechanism of it remains unclear [21].…”
Section: Discussionmentioning
confidence: 99%
“…BMP14 also increased cell proliferation in a time and dose‐dependent manner as well as matrix content . Similarly, BMP12 (GDF7) resulted in upregulation of several tendon markers, including Scx , Tnmd , Col1a1 , and Tnc . Although combinatorial screens with these BMPs have not been extensively studied for TSPCs, stimulation with BMP12 in combination with overexpression of CTGF had an additive effect on the expression of tendon genes .…”
Section: Tspc Culture and Differentiation: Growth Factors Small Molementioning
confidence: 99%